2004
DOI: 10.3201/eid1006.030635
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance amongCampylobacterStrains, United States, 1997–2001

Abstract: We summarize antimicrobial resistance surveillance data in human and chicken isolates of Campylobacter . Isolates were from a sentinel county study from 1989 through 1990 and from nine state health departments participating in National Antimicrobial Resistance Monitoring System for enteric bacteria (NARMS) from 1997 through 2001. None of the 297 C. jejuni or C. coli isolates tested from 1989 through 1990 was ciprofloxacin-resistant. From 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
191
4
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 30 publications
11
191
4
7
Order By: Relevance
“…Patients with quinolone-resistant C. jejuni, treated with fluoroquinolones in Minnesota in 1997 had a median duration of diarrhea of 10 days compared to 7 days in those with sensitive strains [29]. Gupta et al [30] reported 31% patients with ciprofloxacin-resistant Campylobacter were hospitalized for gastroenteritis compared to 3% patients with sensitive strains. In a case control study carried out in 1998-1999 in 290 patients who did not take anti-diarrheal medication for campylobacteriosis, those with ciprofloxacin-resistant strains had a mean duration of diarrhea of 9 days, compared to 7 days in those with sensitive isolates [31].…”
Section: Although 14 Campylobacter Species Have Been Identified In Tmentioning
confidence: 99%
“…Patients with quinolone-resistant C. jejuni, treated with fluoroquinolones in Minnesota in 1997 had a median duration of diarrhea of 10 days compared to 7 days in those with sensitive strains [29]. Gupta et al [30] reported 31% patients with ciprofloxacin-resistant Campylobacter were hospitalized for gastroenteritis compared to 3% patients with sensitive strains. In a case control study carried out in 1998-1999 in 290 patients who did not take anti-diarrheal medication for campylobacteriosis, those with ciprofloxacin-resistant strains had a mean duration of diarrhea of 9 days, compared to 7 days in those with sensitive isolates [31].…”
Section: Although 14 Campylobacter Species Have Been Identified In Tmentioning
confidence: 99%
“…In the Netherlands, van Hees et al (2006) found an inverse relationship between the annual incidence rates of infection from July through September and the rates of floroquinolone and macrolide resistance among Campylobacter isolates (van Hees, 2006). In the U.S., Gupta et al (2004) Campylobacter may persist even after on-farm use of fluoroquinolones has ceased. (Price, 2007) Antimicrobial resistance may also be linked to the method of animal production.…”
Section: Seasonality Can Be Linked To Variations In Antimicrobial Susmentioning
confidence: 99%
“…These infections cause problems in treating illnesses as well as increased rates of illness and death (3). Despite a large body of scientific evidence and a judicial review (1-3) that show harmful results in many persons, some members of the poultry and pharmaceutical industries argue that fluoroquinolone use in food animals has no adverse effects in humans (4) and continue to supply these drugs for use in poultry (2,5). The use of these drugs has caused rapidly increasing resistance rates in most countries.…”
Section: Use In Food Animalsmentioning
confidence: 99%
“…Bayer (manufacturer of the only fluoroquinolone used in poultry in the United States) states that Baytril (enrofloxacin) is used in <1% of US broiler flocks (4). This statistic allows us to estimate how many persons will potentially have an adverse outcome compared to the number of animals receiving fluoroquinolones.…”
Section: Use In Food Animalsmentioning
confidence: 99%